2019
DOI: 10.22149/teee.v3i1.129
|View full text |Cite
|
Sign up to set email alerts
|

Literature Survey of Interleaved DC-DC Step-Down Converters for Proton Exchange Membrane Electrolyzer Applications

Abstract: Recently, the use of electrolyzers for hydrogen production through water electrolysis is of great interest in the industrial field to replace current hydrogen production pathways based on fossil fuels (e.g. oil, coal). The electrolyzers must be supplied with a very low DC voltage in order to produce hydrogen from the deionized water. For this reason, DC-DC step-down converters are generally used. However, these topologies present several drawbacks from output current ripple and voltage gain point of view. In o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 16 publications
(58 reference statements)
0
6
0
Order By: Relevance
“…However, these solutions increase the complexity of the system, cost, and volume. The diodes in Figure 13 are replaced by IGBT to reduce the conduction losses since the on-state resistances of IGBT are smaller than diodes; for low-power applications, MOSFET can also be adopted [60]. Furthermore, an additional capacitor C s is used between the first and second phase to block the DC component of the current flowing through the second phase (i.e., s).…”
Section: Discussion and Future Challengesmentioning
confidence: 99%
“…However, these solutions increase the complexity of the system, cost, and volume. The diodes in Figure 13 are replaced by IGBT to reduce the conduction losses since the on-state resistances of IGBT are smaller than diodes; for low-power applications, MOSFET can also be adopted [60]. Furthermore, an additional capacitor C s is used between the first and second phase to block the DC component of the current flowing through the second phase (i.e., s).…”
Section: Discussion and Future Challengesmentioning
confidence: 99%
“…Therefore, the application of this model for analysis of the electrolyser behaviour regarding the provision of ancillary services in power systems is limited. Regarding the power conversion system, a literature review about the topology of interfaced converters for PEM electrolysers can be found in [19], [20].…”
Section: Electrolyser Models In Literaturementioning
confidence: 99%
“…Recently, several interleaved step-down DC-DC converters have been reported in the literature and are considered as possible candidates to interface DC bus grid and ELs [15]. Among those possible candidates, a three-level interleaved DC-DC buck converter has been selected to realize this work.…”
Section: Of 19mentioning
confidence: 99%
“…Compared to step-up DC-DC converters needed for fuel cell systems [26,27], step-down DC-DC converters requested for PEM EL applications have received less attention from the scientific community. However, recent review works have introduced and emphasized some step-down DC-DC converters for possible interface with PEM ELs [4,15].…”
Section: Presentation and Benefits Of The Three-level Interleaved Dc-mentioning
confidence: 99%
See 1 more Smart Citation